Rodent model to study severe sepsis - Song, Yang (University of Ottawa (Canada), 2007)
Background. The sepsis syndrome is characterized by such clinical changes as hypotension, hypothermia or fever, metabolic acidosis, pulmonary hemorrhage, and death within several hours to days. Antibiotics are a mainstay of treatment and have been repeatedly demonstrated to improve survival in both human studies and animal models of sepsis. Appropriate fluid resuscitation is an important component of the initial therapy for severe sepsis. The antibody against TNF-alpha has improved survival in certain models of sepsis (Reinhart et al. 2001). Hypothesis. Timing of antibiotics is pivotal in survival outcome of sepsis and early fluid resuscitation is crucial in the maintenance of survival rates. Materials & methods. Male Balb/c mice (23--25g) received the cecal ligation and puncture. During the surgery, 1/3 cecum was ligated and 2 18G needle punctures were made from which feces were expressed. During antibiotic treatment strategies, cefotaxime was firstly given at different time points (0, 3, 6 & 12h post-surgery) and thereafter every 6 hours for up to 72 hours. All the mice were given 1ml 0.9% saline fluid at 0 hour post-surgery and continuously every 6 hours for up to 72 hours. For fluid resuscitation 1ml 0.9% saline fluid was started at 0, 3, 6, 9 or 12 hours post-surgery respectively by subcutaneous injection and continuously every 6 hours for up to 72 hours. All the mice were given cefotaxime at 0 hour post-surgery and continuously every 6 hours. Finally, we repeated cefotaxime 12 hours (Group 1) and fluid 12 hours post-surgery (Group 2) groups. Anti-TNF-alpha monoclonal antibody was given at 6 hours post-surgery for both groups. Results. After surgery, untreated mice showed signs of sepsis, such as anorexia, hypothermia and dehydration, and the mortality was 100% within the first 30 hours. The mortalities in cefotaxime 6 & 12 hours post-surgery groups were nearly 100% while cefotaxime 0 & 3 hours post-surgery groups were 0% and 25% respectively. The mortality in fluid resuscitation 12 hours post-surgery group was nearly 100% whereas the other groups (0, 3, 6 & 9 hours) were 12.5% respectively. The mortality of group 1 decreased significantly (Fisher's exact test) compared to the same treatment group without anti-TNF-alpha while the mortality of group 2 did not. Discussion. This model provides consistent results of sepsis, which could enable us to control for treatment factors that are not controllable in human sepsis. In this model we can clearly show the impact of timing of antibiotics on survival. Despite early antibiotics administration (time 0), mortality of this model is still high when fluid resuscitation is delayed. Anti-TNF-alpha can decrease the mortality under condition that fluid resuscitation are given at an early time point.
Keywords: Biology, Microbiology.